Molecular methods to study protein trafficking between organs. Issue 6 (18th December 2022) - Kreissl, Felix K.; Banki, Michael A.; Droujinine, Ilia A.
Abstract: Interorgan communication networks are key regulators of organismal homeostasis, and their dysregulation is associated with a variety of pathologies. While mass spectrometry proteomics identifies circulating proteins and can correlate their abundance with disease phenotypes, the tissues of origin and destinations of these secreted proteins remain largely unknown. In vitro approaches to study protein secretion are valuable, however, they may not mimic the complexity of in vivo environments. More recently, the development of engineered promiscuous BirA* biotin ligase derivatives has enabled tissue‐specific tagging of cellular secreted proteomes in vivo. The use of biotin as a molecular tag provides information on the tissue of origin and destination, and enables the enrichment of low‐abundance hormone proteins. Therefore, promiscuous protein biotinylation is a valuable tool to study protein secretion in vivo.